Flexible Electronics: Bio‐Inspired Chemical Fabrication of Stretchable Transparent Electrodes (Small 28/2015). Issue 28 (July 2015) - Yu, You; Zhang, Yaokang; Li, Kan; Yan, Casey; Zheng, Zijian
<x xml:space="preserve">Abstract</x> Bio‐inspired, stretchable, and transparent conducting electrodes (STCEs) are fabricated by Z. Zheng and co‐workers in a solution‐processed approach. On page 3444, natural veins of leaves are used as the templates and chemically modified by functional polymers for the deposition of metal thin films at ambient conditions. These transparent electrodes show excellent electro‐optical properties at large strains, due to the large vein‐free areas and flexible polygonal unit cells in the veins, ideal for flexible and stretchable optoelectronic devices.